Extraction and identification of bioactive components in Sida cordata (Burm.f.) using gas chromatography–mass spectrometry - Ganesh, Mani (J Food Sci Technol, 2017)
Sida cordata (Burm.f.) is a pineal tropical plant in the family Malvaceae that is found throughout India and used to treat various diseases and ailments in many complementary and alternative medicine systems. This study identified the bioactive components present in whole-plant ethanol extracts of S. cordata using gas chromatography–mass spectrometry (GC–MS). Based on their retention times (RT) and mass-to-charge ratios (m/z), 29 bioactive compounds were identified: nonanoic acid, vitamin D(3), 3-trifluroacetoxypentadecane, α-d-glucopyranoside, O-α-d-glucopyranosyl-(1.fwdarw.3)-α-d-fructofuranosyl,3,7,11,15-tetramethyl-2-hexadecan-1-ol, octadecanoic acid, ethyl ester, phytol, 9,12-octadecadienoic acid, methyl ester (E,E), 9,12,15-octadecadienoic acid, methyl ester (Z,Z,Z), oleic acid, 1,2-15,16-diepoxyhexadecane, 3-hexadecyloxycarbonyl-5-(2-hydroxyethyl)-4-methylimidazolium ion, methoxyacetic acid, 4-tetradecyl ester, 1,2-benzenedicarboxylic acid, mono (2-ethylhexyl) ester, 1-iodo-2-methylundecane, dodecane, 2,6,10-trimethyl-, 2-piperidinone-N-[4-bromo-n-butyl]-, squalene, octadecane-1-(ethenyloxy)-, Z,Z-2,5-pentadecadien-1-ol, 1-hexadecanol, 2-methyl-, spiro[androst-5ene-17,1′-cyclobutan]-2′-one-3-hydroxy-, (3a,17a)-, diethylene glycol monododecyl ether, vitamin E, cholestan-3-ol, 2-methylene-, (3a,5a)-, 2H-pyran, 2-(7-heptadecynyloxy)tetrahydro-, and cis-Z-α-bisabolene epoxide. The presence of various bioactive compounds justifies the use of this plant for treating various ailments by traditional practitioners.